Clinical and metabolic correlates of cerebral calcifications in Sturge–Weber syndrome. (11th April 2017) - Pilli, Vinod K; Behen, Michael E; Hu, Jiani; Xuan, Yang; Janisse, James; Chugani, Harry T; Juhász, Csaba
Abstract : Aim: To evaluate clinical and metabolic correlates of cerebral calcifications in children with Sturge–Weber syndrome (SWS). Method: Fifteen children (11 females, four males; age range 7mo–9y, mean 4y 1mo) with unilateral SWS underwent baseline and follow‐up magnetic resonance imaging (MRI) with susceptibility weighted imaging (SWI), glucose metabolism positron emission tomography (PET), and neurocognitive assessment (mean follow‐up 1y 8mo). Calcified brain volumes measured on SWI were correlated with areas of abnormal glucose metabolism, seizure variables, and cognitive function (IQ). Results: Ten children had brain calcification at baseline and 11 at follow‐up. Mean calcified brain volume increased from 1.69 to 2.47cm 3 ( p =0.003) in these children; the rate of interval calcified volume increase was associated with early onset of epilepsy (Spearman's rho [ r s ]=−0.63, p =0.036). Calcified brain regions showed a variable degree of glucose hypometabolism with the metabolic abnormalities often extending to non‐calcified cerebral lobes. Larger calcified brain volumes at baseline were associated with longer duration of epilepsy ( r s =0.69, p =0.004) and lower outcome IQ ( r s =−0.53, p =0.042). Interpretation: Brain calcifications are common and progress faster in children with SWS with early epilepsy onset, and are associated with a variable degree of hypometabolism, which is typically more extensive than the calcified area. Higher calcified brain volumes may indicate a risk for poorer neurocognitive outcome. What this paper adds: Brain calcifications progress faster in children with Sturge–Weber syndrome (SWS) and early‐onset epilepsy. Hypometabolism often extends beyond calcified brain regions. Calcified brain volume may be an imaging biomarker for cognitive outcome in SWS.